Anthropometric and physiological characteristics of junior elite volleyball players - Duncan, M. J.; Woodfield, L.; Al-Nakeeb, Y. (British Journal of Sports Medicine, 2006)
ABSTRACT Objectives: To investigate the anthropometric and physiological characteristics of junior elite volleyball players.